PELATIHAN GOOD FARMING PRACTICES UNTUK MENINGKATKAN PRODUKTIFITAS TERNAK DOMBA PADA CV. SULTAN FARM JEMBER - Rinda Nurul Karimah; Naning Retnowati; Fredy Eka Ardhi P; Dewi Kurniawati (Bajang Institute, 2024)
Sheep are small ruminants with quite high prospects, especially in providing a source of animal protein. CV. Sultan Farm is a company that operates in the field of breeding, fattening, and trading sheep. This company was established in 2019 until now and has supplied many meat sheep in the Jember area and surrounding areas. Increase in the number of CV sheep. Sultan Farm's breeding process is still less than optimal. Therefore, to increase livestock productivity, CV. Sultan Farm requires training on how to apply GFP to sheep properly. This training activity aims to increase partners' knowledge about Good Farming Practices (GFP) or good Livestock Cultivation Guidelines to increase livestock population, production, and productivity, and improve the quality of livestock products, in the form of quality meat, safe and suitable for consumption. The methods used were surveys, delivery of training materials, and direct practice of sheep cultivation. Conclusions from the results of this activity: 1) The sheep cultivation training activity by following Good Farming Practices (GFP) given to participants ran smoothly and successfully; 2) The final evaluation of the results of the activity shows that the partner breeders have a good understanding of the GFP procedure as demonstrated by the ability to describe and practice sheep cultivation procedures/techniques correctly and appropriately